'No Condition IS Permanent': Informal Transport Workers and Labour Precarity in Africa's Largest City. (20th March 2017) - Agbiboa, Daniel E.
Abstract: This article pieces together an understanding of everyday life grounded in the social imagination and everyday experiences of informal transport workers (ITWs) in Lagos, Nigeria's commercial capital and Africa's largest city. The article has two core objectives: to elevate the everyday practices of ITWs to the status of a critical concept in order to advance a sociology of everyday life, and to ground these practices on the precarious rhythm of everyday life as lived by people with the experience of radical uncertainty. By using crisis as a context of action and meaning, the article shows how uncertainty serves as a social resource that ITWs leverage to negotiate the precarious nature of everyday life and to make the most of their time. This foregrounding of uncertainty enhances our hitherto tenuous grasp of labour precarity, informal agency and the everyday struggle for survival in Africa's informal transport sector.